Adsorption kinetics and optimum conditions for Cr(VI) removal by activated carbon prepared from luffa sponge. Issue 17 (8th April 2016) - Miao, Ming-sheng; Wang, Yan-na; Kong, Qiang; Shu, Li
Abstract: Activated carbon (AC) prepared from luffa sponge was firstly used as an adsorbent to remove Cr(VI) from aqueous solution. The Cr(VI) adsorption behaviors of AC under different conditions, including initial Cr(VI) concentration, quantity of AC, solution pH, and temperature were investigated. The optimal conditions for adsorption of Cr(VI) by AC were pH = 1, initial Cr(VI) concentration = 80 mg/L, T = 303 K, and AC content = 1.6 g/L. The adsorption kinetics could be described by the pseudo-second-order model. Fourier transform infrared spectroscopy was used to investigate the sorption mechanism. Some functional groups such as C–O and O–H were formed on the carbon surface, which could then react with Cr(VI). The surface structure of AC before and after adsorption was analyzed by scanning electronic microscopy. Adsorbed ions choked some of the pores in AC after adsorption. The Brunauer–Emmett–Teller surface area and average pore size of the AC were 834.13 m 2 /g and 5.17 nm, respectively. The maximum adsorption of Cr(VI) by AC was 149.06 mg/g, which makes AC prepared from luffa sponge promising for removing Cr(VI) from wastewater.